To What Extent Is Aquaculture Socially Beneficial? A Theoretical Analysis. (20th June 2016) - Regnier, Esther; Schubert, Katheline
Abstract : This article offers a theoretical analysis of the impact that the introduction of aquaculture has on wild fish stocks and consumer utility, taking into account three key components: (1) the dependence of aquaculture on reduction fisheries for the feeding of the farmed species; (2) biological interactions between the wild edible species—the predator—and the wild feed species—the prey; and (3) consumer preferences for wild and farmed fish. Fisheries are in open access, while the aquaculture sector is competitive. We show that when biological interactions are moderate, the introduction of aquaculture is beneficial in the long run: it improves consumer utility and alleviates the pressure on the edible fish stock. Results are deeply modified when biological interactions are strong: the stock of edible wild fish is reduced and the introduction of aquaculture may even cause a decrease in consumer utility. We then explore the consequences of improving aquaculture efficiency and the sensitivity of consumer preferences to the farmed fish characteristics, in the case where biological interactions are absent. Lastly, we analyze how our outcomes on the entry of aquaculture are affected when the wild edible fishery is optimally regulated, in combination with different assumptions on the regulation of the feed fishery. Results are again conditional on the intensity of biological interactions.